Art, equality and learning pedagogies against the state - Atkinson, Dennis 1947-; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
In this book the notions of real learning and equality are approached as processes of becoming leading to the figuration of new worlds through local curations of learning and practice. Though its main theses are mainly grounded in the context of art practice and education they have a much wider application to other (perhaps all) contexts of learning through the notions of pedagogies against the state and pedagogies of the event. Learning is conceived as a political act rather than, for example, an incremental process of psychological or sociological development.
Art, Equality and Learning -- Dedication -- Table of Contents -- Acknowledgements -- Introduction -- The Gap and Magritte -- Chapter 1: Pedagogies against the state: Initial Thoughts about Learning -- Introduction -- Two anecdotes -- Early encounters: a video of a child painting -- An ethics of pedagogy -- Being and event -- That which is not yet -- Pedagogies against the state -- Concluding comments and a third 'event' -- Chapter 2: Theorising the subject -- A curious contradiction -- Brief overview of some theories of the subject -- Foucault -- Lacan--Badiou -- Philosophical Context -- Change and social orders -- The obstacle of audit -- Subjectivization and learning -- A local event of learning -- Truth, Subtractive ontology and excessive subject -- Appearance and transcendental -- Truth and pedagogy -- Ranciere, pedagogy and equality -- Summary -- Chapter 3: Subjectivities and school art education: mourning and openings -- Introduction -- Mourning the past -- Approaching the future -- The subordination of teaching to learning -- Changing the subject -- Encounters of learning -- The gallery as a site for learning -- Chapter 4: Some ethical and pedagogical issues: Forcing, Subjectivization and Desire -- Subjectivization -- Forcing -- Chapter 5: Tensions in art in education -- Introduction -- The negation of origins -- Icons and the new -- School Art Performances and Iconographies in England -- Thinking the pedagogical space differently: addressing the tensions between contemporary art and school art practices -- Redistributions of pedagogic spaces -- Conclusion -- Conclusion -- Chapter 6: Looking awry at assessment and the abrogation of becoming -- Introduction -- Zizek: Sublime object of ideology -- Why has the assessment process itself assumed such a form? -- The rise of aesthetic discourse -- Ranciere's three regimes of art -- Poiesis and praxis --Transmissibility and intransmissibility -- How is this relevant for assessment of learning? -- Difference and becoming: assessment and some concluding remarks -- Chapter 7: The artist-teacher --Introduction -- The artist teacher scheme -- Badiou: truth, art and education -- Creativity: negation, destruction, substraction -- Artist-Teacher Narratives -- ANNIE DERBYSHIREDANNY MURPHY -- JUDE THOMAS -- TESSA HODSON -- COMMUNITIES OF PRACTICE -- KEEPING THE ARTIST-TEACHER INFINITE -- SO WHAT DO RECENT MOVEMENTS IN CONTEMPORARY ART AND PEDAGOGY IMPLY FOR THE ARTIST-TEACHER? -- THE PEDAGOGIC TURN -- CONCLUDING REMARKS -- CHAPTER 8: MULTICULTURALISM, BEING-WITH AND THE RADICANT -- YINKA SHONIBARE AND THE EXPANDED FIELD -- MULTICULTURALISM -- EDUCATION AND MULTICULTURALISM -- WE DON'T NEED TO UNDERSTAND THE OTHER! -- ON BEING SINGULAR PLURAL -- NICOLAS BOURRIAUD: ROOTS AND RADICANTS -- Ethics and local curations of learning -- Giving an account of oneself and ethical responsibility -- Critique of pedagogised subjects -- Lacan and Zizek: ethics of the real -- The ethics of Badiou and its relevance for pedagogy -- Ethic of truth -- Ethics of wonder -- Postscript -- Autonomy and self-emancipation -- Communism of the will
Electronic reproduction
Keywords: Art -- Study and teaching; Education -- Political aspects; Education and state